Nilai – Nilai Solidaritas Sosial dalam Kelompok Bantengan Adi Putra Nuswantara - Atikah Nur Izzah; Rizkiati Amalia; Muhammad Fathkhur Rohman Al falakh; Rois Imron Rosi (Universitas Lambung Mangkurat, 2024)
Indonesia is a country that rich in diversity of customs, tribes, races and traditions. Talking about traditions in Indonesia, each region has a cultural heritage that has been passed down from their ancestors to the present. One tradition that is still maintained in East Java is the Bantengan art tradition of the Adi Putra Nuswantara group. This research aims to find out the values of social solidarity in the Adi Putra Nuswantara that built through social interaction within group. The group that still existed from its firstly organized until now will be important to be studied. The result of this study will be important for studying some ways in conserving any cultural heritage. The theory used in this research is Emile Durkheim’s theory of social solidarity. The method applied in this research is a qualitative descriptive research method. The research result stated that the solidarity values of the Adi Putra Nuswantara group were formed because of the values of togetherness, kinship, deliberation, mutual assistance and harmony. With the values that exist in each member of the group, mutual solidarity is realized between the group of Adi Putra Nuswantara. These values became important in maintaining the existence of the group and as an effort to conserve cultural heritage